Management of Environment-Based Curriculum in Senior High Schools: Barriers and Challenges - Komariah, Komariah; Haryanto, Haryanto; Putera, Agustian Ramadana (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This study investigates the management system of an environment-based curriculum in senior high schools, specifically in Bandung City, encompassing elements of curriculum planning, implementation, and evaluation. Conducted as qualitative research, this investigation draws its primary data from the vice principal in charge of curriculum development. The data collection techniques employed include interviews and documentation, with the primary research instruments being observation guidelines, interview guidelines, and document analysis. The study was conducted at three schools: SHS 3, SHS 12, and SHS 20 Bandung, with teachers and vice principals serving as informants. The findings indicate that 1) curriculum planning involves all school members participating in the developmental process, 2) curriculum implementation refers to a pre-established learning plan (RPP) and Teaching Modules, with the theme of environmental appreciation conveyed organically, and 3) evaluation outcomes guide school decision-making processes, with subsequent actions being determined to enhance and foster participatory, effective, and efficient learning activities. This research holds implications for improving environment-based curriculum management in senior high schools, offering valuable insights for stakeholders striving to enrich learning outcomes and foster environmental consciousness among students.